Ambiguity Preferences and Portfolio Choices: Evidence from the Field - Bianchi, Milo; Tallon, Jean-Marc (Management Science, 2019)
We match administrative panel data on portfolio choices with survey data on preferences over ambiguity. We show that ambiguity averse investors bear more risk, due to a lack of diversification. In particular, they exhibit a form of home bias that leads to higher exposure to the domestic relative to the international stock market. While more sensitive to market factors, their returns are on average higher, suggesting that ambiguity averse investors need not be driven out of the market for risky assets. We also show that these investors rebalance their portfolio more actively and in a contrarian direction relative to past market trends, which allows them to keep their risk exposure relatively constant over time. We discuss these findings in relation to the theoretical literature on portfolio choice under ambiguity. The online appendix is available at https://doi.org/10.1287/mnsc.2017.3006 . This paper was accepted by Han Bleichrodt, decision analysis.